Dari Webtoon ke Buku Fisik: Platform Digital terhadap Kreativitas dan Pemasaran Sastra Generasi Z (Pusat riset dan Inovasi Nasional, 2026)
This research examines the influence of the Webtoon platform on the creativits and literary marketing of Gen – Z in Indonesia, with a focus on the increasingly common trasition of digital content to physical books. The research background is grounded in the rapid growth of Webtoon as a platform for illustrated stories accessed by millions of young users via mobile devices, enabling affordable creative expression, but often encountering adaptation challenges to print formats due to differences in distribution and monetization. The primary objective is to analyze how Webtoon shapes the creative processes of young writers and their literary marketing strategies. The research method is qualitative, involving in-depth analysis of 10 popular Webtoons on the Webtoon platform that have been adapted into physical books, with emphasis on narrative elements, visuals, community interactions, and marketing patterns. Findings reveal that Webtoon fosters creativity through collaboration features and instant feedback, resulting in more dynamic original stories, while the transition to physical books enhances market visibility by 20-30% via digital promotion, although hindered by copyright complexities and production costs. The implications of this research underscore the importance of collaboration between traditional publishers and Webtoon to establish a hybrid literary ecosystem that sustainably supports Generation Z talent.